Restoring Baird's image - McLean, Donald F. (London, United Kingdom Institution of Electrical Engineers, 2000)
In the late 1920s, John Logie Baird - considered to be the inventor of television - was experimenting with 'phonovision' in which he attempted to record television signals onto gramophone discs. His efforts were mostly unsuccessful and this technology largely forgotten, until the 1980s when Don McLean came across the discs and set about restoring them with modern computer-based techniques. The recovery of these images gives us a fascinating glimpse of what the earliest television was like (before official TV services started). As well as helping to explain a poorly understood period of television history, this unique book sheds new light on the activities of John Logie Baird and the definition and invention of television itself.
Electronic reproduction.
Keywords: Baird, John Logie -- 1888-1946.; Television -- History. -- Great Britain; Television -- Technological innovations -- History. -- Great Britain; Video recording -- History. -- Great Britain; Inventors -- Scotland -- Biography; Electronic books